Measurement of the σ- charge radius by σ--electron elastic scattering - Eschrich, I.; Krüger, H.; Simon, J.; Vorwalter, K.; Alkhazov, G.; Atamantchouk, A. G.; Balatz, M. Y.; Bondar, N. F.; Cooper, P. S.; Dauwe, L. J.; Davidenko, G. V.; Dersch, U.; et al. (Elsevier, 2001)
The σ- mean squared charge radius has been measured in the space-like Q2 range 0.035-0.105 GeV2/c2 by elastic scattering of a σ- beam off atomic electrons. The measurement was performed with the SELEX (E781) spectrometer using the Fermilab hyperon beam at a mean energy of 610 GeV/c. We obtain (rch2σ- = (0.61 ± 0.12(stat.) ± 0.09(syst.)) fm2. The proton and π- charge radii were measured as well and are consistent with results of other experiments. Our result agrees with the recently measured strong interaction radius of the σ-. © 2001 Elsevier Science B.V. All rights reserved.
Keywords: Elastic scattering; Electromagnetic form factors; Hadron strong and electromagnetic radii; Hadron-induced elastic scattering at high energy; Hyperons